PELATIHAN PEMBUATAN BAHAN AJAR MENGGUNAKAN CAMTASIA STUDIO DI SMK N TEMBARAK TEMANGGUNG - Edhy Sutanta; Muhammad Sholeh; Erna Kumalasari Nurnawati (LPPM IST AKPRIND Yogyakarta, 2019)
Community Service (PkM) is one of the obligations that must be carried out by lecturers. This time the PkM was held at Tembarak Temanggung Vocational School on December 7, 2018. The PkM organizer was the Lecturer Team of the Informatics Engineering Department, IST AKPRIND Yogyakarta, while the activity participants were Teacher of Tembarak Temanggung Vocational School N which totaled 55 people. PkM was held for 40 hours in the form of activities in the form of lectures, delivery of questions and answers and exercises. The training material is the making of teaching materials using Camtasia Studio software. The implementation of PkM which synergizes the needs of partners and the competence of the PkM Team is an excellent model, so it needs to be continued. This PkM still needs to be followed up, in the form of Training and Assistance for Writing Scientific Articles in the National Journal.